Bibliometric Analysis of Green Economy Learning for Children (1996-2023): Current Status and Future Directions - Utami, Nunung Nurastuti (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This research aims to map research conducted by reputable journals indexed by Scopus on Science Direct from 1996 to 2023 regarding the theme "Green economic learning for children." Data was obtained from the Scopus website (Science Direct), using the keywords: "Green Economy" AND "Learning for Children," with a range of publication years 2016-2023, in the field of Social Sciences, documents: research articles, and open access. Based on the criteria, there were 54 articles, and the analysis used R – biblioshiny software. The analysis technique uses bibliometrics using R biblioshiny software. The results of the bibliometric analysis revealed four quadrants, namely the motor theme quadrant or driving topic, represented by future energy transition, sustainability, transition planning, green, and urban. This topic must be developed considering topics that are important for the future. The special theme quadrants are governance, insight, and students: learning and teachers. The emerging or decreasing theme quadrants represent environmental, economic, and emissions evidence and perspectives. The basic theme quadrant is represented by the themes: learning, education, COVID, climate, strategy, and pathways. The themes from the results of this research recommended for further development are themes related to the keywords governance, insight, students, learning, and teachers, especially themes related to innovative learning models for children.